El uso didáctico de Google Sites en la construcción compartida del conocimiento - Alba Ambròs Pallarès (Universidad de Cádiz, 2017)
The proposals follow the key competences approach and pretend to face everyday teaching practices with the range of options ICT offers. The paper starts with the description of some actual teaching practices in order that the reader can value the potential they have. Then, learning and knowledge technologies will be treated through a reflection of the challenges that Google Sites offers to the society. A reflection about the actual possibilities of working with these web environment tools will close the paper.